(untitled) (Research, Society and Development, 2021)
The research aimed to identify the relationship between the use of a pacifier and the early interruption of breastfeeding through the findings of the scientific literature. This is an integrative review carried out in March 2020 through findings in the Virtual Health Library, PubMed / Medline and Scientific Eletronic Library Online with the health descriptors: Breast Feeding / Breast Feeding, pacifiers / Pacifiers; and the irregular keyword: interruption of breastfeeding / interruption of breast feeding, using the Boolean operator and for the crossing of the terms used. The search for findings in the literature resulted in six articles. It was evidenced that some mothers use the pacifier as an object of comfort to their baby in their first months of life and that this practice has contributed to the early interruption of breastfeeding due to the shape of the pacifier tip being inversely proportional to that of the nipple, an aspect which makes the baby reject it, since sucking on the nipple is an arduous and tiring task, unlike what is done with a pacifier. In this sense, the use of the pacifier is pointed out as a predictive factor for the early interruption of breastfeeding, making it necessary to intensify the practice of educational strategies that aim to clarify and guide about the risks of using a pacifier during breastfeeding.